Trehalose enhances macrophage autophagy to promote myelin debris clearance after spinal cord injury - Zhida Ma; Congpeng Meng; Xiang Wang; Yuanzhe Zhao; Jingwen Wang; Yihao Chen; Yiteng Li; Yan Jiang; Fangru Ouyang; Jianjian Li; Meige Zheng; Li Cheng; et al. (Cell & Bioscience)
Abstract Background Myelin-laden foamy macrophages accumulate extensively in the lesion epicenter, exhibiting characteristics of autophagolysosomal dysfunction, which leads to prolonged inflammatory responses after spinal cord injury (SCI). Trehalose, known for its neuroprotective properties as an autophagy inducer, has yet to be fully explored for its potential to mitigate foamy macrophage formation and exert therapeutic effects in the context of SCI. Results We observed that trehalose significantly enhances macrophage phagocytosis and clearance of myelin in a dose-dependent manner in vitro. In vivo, trehalose administration markedly reduced myelin debris accumulation, inhibited foamy macrophage formation, suppressed inflammatory responses, decreased fibrotic scarring, and promoted axonal growth and motor function recovery after SCI. These beneficial effects of trehalose may be related to the overexpression of transcription factor EB (TFEB), a key regulator of the autophagy-lysosomal system, which can rescue autophagic dysfunction in foamy macrophages and inhibit inflammatory responses. Additionally, the effects of trehalose on macrophages were abolished by chloroquine, an autophagy inhibitor, suggesting trehalose’s potential as a therapeutic candidate for enhancing myelin debris clearance post-SCI. Conclusions Our findings underscore the pivotal role of trehalose in modulating myelin debris clearance within macrophages, providing new perspectives for the treatment of spinal cord injury. Graphical abstract